Global and regional lung function in cystic fibrosis measured by electrical impedance tomography. Issue 11 (29th April 2016) - Lehmann, Sylvia; Leonhardt, Steffen; Ngo, Chuong; Bergmann, Lukas; Ayed, Ines; Schrading, Simone; Tenbrock, Klaus
Summary: Background: Electrical impedance tomography (EIT) delivers information about global and regional ventilation. Linearity of EIT during tidal breathing is known. We investigated the feasibility of EIT during lung function tests in pediatric patients with cystic fibrosis (CF) and healthy controls. Methods: Eleven CF patients and 11 age‐matched controls underwent spirometry and simultaneous EIT. Global EIT results were scaled to spirometric forced vital capacity (FVC). Subsequently, global and regional "EIT‐spirometry" was calculated and correlated with clinical findings, radiology, and lung function results before and after bronchospasmolysis (BSL). Results: Spirometry and global EIT results correlated essentially (r 2  = 0.71–1.0, P  < 0.001). While lung function results were comparable for both groups, EIT demonstrated inhomogeneous ventilation and individual changes after BSL. Conclusions: EIT changes during forced expiration correlate with lung function parameters, clinical findings, and radiology. Regional analysis of EIT illustrates regional lung function and visualizes individual therapeutic effects.Pediatr Pulmonol. 2016;51:1191–1199. © 2016 Wiley Periodicals, Inc.